The Use of Women as Suicide Bombers by Boko Haram in Nigeria: Array - Oghuvbu, Ejiroghene Augustine (Acta Universitatis Danubius. Relationes Internationales, 2021)
The study examines the current events of suicide bombings in Nigeria; an incident that is foreign to the nation. Boko Haram growing level of using women and young girls as suicide bombers raises curiosity among scholars of strategic and security studies. Women's status as weaker sex appears to have vanished in light of the reality of incorporating a gender perspective into all phases of terrorist groups' lethal actions. Why has it become more profitable for terrorist organizations to utilize women to assist or carry out their operations? While this has become problematic and has generated questions about the strategic reasons of women’s activities as suicide bombers, it is becoming very clear that the relationship between women and terrorism cannot be ignored. This study therefore, examines the concept of suicide bombing, women as pawn and why women are been used to carry out suicide bombing by Boko Haram. The consequences under Municipal and universal laws are also examined. The study therefore, recommends that women and other young people should be well educated about the risks of being used by Boko Haram to combat the state and thereby endangering the lives and properties of innocent citizens.